DIALECTICS OF INTIMACY: A STUDY IN SELECT GRAPHIC NARRATIVES - RAINA, SHRIYA (IISER Mohali, 2023)
This thesis proposes intimacy as a site and method in the diegetic universes of three graphic narratives based in geopolitical conflict. It analyzes Munnu (2015), Vanni (2019), and Welcome to the New World (2020), to study how intimacy operates as a dialectical engagement of two sovereign consciousnesses: self and alien. Violence is the constitutive operant of the dialectic and mediates the most fundamental engagement between the two components. Their transformations and modifications in particular instances of intimacy are matter of textual analysis. The thesis utilizes the proposed dialectical universe to study select graphic narratives and negotiations of and around violence in the registers of embodiment, death, and everyday. It is possible because of the aesthetic and political centrality of violence to comics as a medium, the representative contexts, and the fundamental presence of intimacy in the primary texts, i.e., a conversation at the level of form and content. The project studies this by further interrogating the contributions of a philosophically sensitized reading of comics to current discourses around reclaiming mainstream global geopolitics. Here, intimacy is derived from the field of intimacy geopolitics and therefore, in going beyond inter-personal relationships, it transcends scale and proximity. Textual analysis raises the following questions. Is intimacy operational only in receiving and circulating violence, or does it also condition it in the process? If it does, what is its politics, and how does it figure in the ethics of doing and reading ethnographic comics? Intimacy is a political project with ethical consequences for any representation from geopolitical conflicts. This dialectic is my optic into the ethics and politics of doing ethnographic graphic narratives. It is also the study of the emergence of the politics and ethics of comics that involves reader, writer, and character. This thesis is a methodological and epistemological shift from violence 8to intimacy as an optic and site of investigation, going beyond the naturalized co-incidence between zones of explicit violence and the context of representation in the medium of comics. Keywords: Violence, Comics, Intimacy geopolitics
Keywords: geopolitics; diegetic